Conversion of Oximes into Carbonyl Compounds with Glycinium Chlorochromate Supported Onto Silica Gel - HEKMAT SHOAR, RAHIM; REZAEI, AKRAM; HAGHIGHI, MASOUMEH; JAFARI OJGHAZ, AZADEH; KHOSROSHAHI, MINOO; MOSHREF JAVADI, NEGAR (Asian Journal of Chemistry, 2010)
Glycinium chlorochromate supported onto acidic silica gel was reacted with oximes and converts them to their corresponding carbonyl compounds in good yields.